Comparative Analysis of Citizen Complaints and Public Authority Interaction: A Study of the EU - Seidalina, Zhanna (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2025)
Compliance with human and civil rights is a key task of governments. An effective institution for citizens’ appeals, particularly through complaints, enables interaction with public authorities to restore rights that have been violated. The study aims to compare and analyse administrative and legal aspects of the institution of citizens’ appeals in European Union countries, Ukraine, and the Republic of Kazakhstan. Methods such as formal legal analysis, comparative legal analysis, statistical observation, and content analysis were employed. The results indicate that the legal frameworks of all examined jurisdictions provide citizens with the constitutional right to submit complaints to state authorities, although only a few explicitly define the term “complaint.” A comparative analysis demonstrates that the decentralization of the Commissioner’s institution in Kazakhstan enhances accessibility, improves monitoring of human rights protection, and strengthens citizens’ trust in public authorities. The findings underline that well-structured complaint mechanisms and decentralised ombudsman systems contribute to more transparent, responsive, and citizen-oriented governance.